EDUKASI DAN KONSELING POLA ASUH ORANG TUA MENDUKUNG PROGRAM PENCEGAHAN STUNTING DI KELURAHAN LAPPA - Alawiyah, Desi; Surianti, Surianti; Suriati (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2025)
Stunting is a serious health problem in Indonesia, with a prevalence of 27.67%, far above the WHO standard of less than 20%. This condition is recognized as the "golden period" of child development (the First 1,000 Days of Life), which, if not optimally managed, can cause permanent damage. Handling stunting is not only related to nutrition but also involves the role of the family, especially both parents, in care. This study aims to understand parenting patterns, analyze family support, and evaluate the implementation of good parenting education and counseling for stunting prevention in Lappa Village. This study used a qualitative approach with a descriptive case study type, which aims to describe the subjective behavior of the studied. The study location is Lappa Village, North Sinjai District, Sinjai Regency, and was conducted from March to May 2024. The study subjects included 5 parents and close family members, 2 Posyandu cadres, and 2 health workers. Data were collected through interviews and observations. Parenting Styles: Parenting styles are crucial in preventing stunting, influenced by education levels, knowledge, and good feeding practices. Mothers with higher education are more receptive to nutrition and health information. A mother's knowledge of nutrition and proper feeding practices is crucial. A mother's psychological well-being, such as anxiety, also influences parenting styles. Family Support: Family support, particularly the role of the father, is crucial. Fathers who are cooperative and actively involved in childcare, including helping with housework and providing mental support, contribute to stunting prevention. Lack of cooperation between husband and wife in establishing parenting rules can hinder prevention efforts. Education and Counseling: Education and counseling services provided at integrated health posts (Posyandu), including monitoring the Child Health Card (KMS), providing vitamins, providing PMT (Food and Nutritional Supplements), and providing education on complementary foods (MPASI) and balanced nutrition, play a crucial role in improving parental understanding and behavior. The 'Isi Piringku' (My Plate) socialization campaign was also effective in changing maternal behavior related to feeding. The study's conclusions indicate that good parenting styles, supported by education, knowledge, and proper feeding practices, as well as strong family support, are highly effective in preventing stunting. Education and counseling conducted by integrated health posts (Posyandu) and health workers play a vital role in improving parents' understanding and skills. The implications of this research are the importance of strengthening education and counseling programs that involve both parents and family support, as well as enhancing the role of Posyandu cadres to achieve optimal stunting prevention.